Teaching Makes the Difference! On the Quality of Geography Classes - Dickel, Mirka (Journal of Geography Education, 2024)
This paper determines the quality of geography classes from the point of view of teaching, which is dialogically directed towards self-reflexive learning. This decidedly pedagogical argumentation makes it possible to find a way of dealing with pedagogical difference and the resulting antinomy of teaching as the formation of maturity under coercion. Klaus Prange defines teaching in his Operative Pedagogy as pointing–a perspective this paper subscribes to. The basic form of pointing, its scales, articulation schemes, pointing forms and figures serve as a starting point to highlight the principles of the normativity of teaching. Determining teaching quality normatively has the advantage of making it verifiable and assessable, teachable and learnable. The subject matter of geography is inscribed in the acts of pointing.